A Review on Geo3o1 for 3D Georeferencing Accuracy Assessment of State-of-the-Art Sensor Dependent Orientation Model - H. Topan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Geo3o1 is a Matlab tool for 3D georeferencing accuracy retrieval for Pléiades 1A/1B/Neo, SPOT 6/7 and Göktürk-1 stereo or triplet primary panchromatic images. Even though the orientation model was settled by the image providers, the main contribution of Geo3o1 is the two-stage adjustment computation. Moreover, exterior orientation parameters’ efficiency and validation, and also the correlation between interior and exterior orientation parameters could be analysed. Geo3o1 is capable of processing stereo or triplet images. The case study was handled with the panchromatic primary triplet images of Pléiades 1A. 171 points measured by GNSS observations were used. The accuracy on the ground was estimated at the centimetre level for GCPs, while the accuracy for ICPs was naturally coarser at ∼ ± 1 GSD in bundle adjustment. The external orientation parameters’ effectiveness and validation, and co- and cross-correlations were also investigated. The test site covers a hilly, mountainous area in Zonguldak, Türkiye.